Moderating role of productivity on diversified conglomerates and performance: the case of Malaysia - Alex, Kwaku Gyan (Emerald Group Publishing Ltd., 2017)
Purpose – The purpose of this paper is to investigate the previous mixed findings in the relationship between diversification and firm performance. Using international and industrial conglomerates, the paper introduces productivity as a moderating variable to ascertain whether the mixed views in the diversificationperformance nexus is due to variations in productivity. The findings in both proxies of performance (q and return on asset (ROA)) show that productivity is not a significant moderator in the diversificationperformance link, except that under industrial conglomerates productivity enhances ROAs significantly. Meanwhile, the results show that diversification either has no significant value on firm performance or relates negatively with performance – a contrasting result to the hypothesis of this study. Design/methodology/approach – This study adopts diversification measurement, categorisation approach and the methodology used in the work of Fauver et al. (2004) and the subsequent modification by Lee et al. (2012). This study, however, investigates themoderating effect of productivity on diversified firms and not ownership as shown in the previous studies. Performance is measured by two proxies to show robustness of the study. ROA is an accounting tool and Tobin’s q reflects a market-based performance of the firm. Findings – The results show that productivity has no moderating impact on a market-based performance of a diversified firm. Regarding ROA, results show a split in finding by showing that productivity has no significant impact on international diversification; however, for industrial diversification, results show significant impact. Originality/value – The paper adds to knowledge of finance by ruling out the view that the inconsistencies in the diversification and performance nexus in emerging economies could be due to vagaries in productivity. It is confirmed that productivity technically does not strengthen the link between diversification and performance: suggesting that factors other than productivity could establish a maximal impact on that link to minimise the inconsistencies in the findings on diversification-performance link.